2008
DOI: 10.9755/ejfa.v20i1.5182
|View full text |Cite
|
Sign up to set email alerts
|

Microbial quality of camels raw milk in central and southern regions of United Arab Emirates

Abstract: The goals of this study were to assess the possible hazards that might occur as a result of consuming camel's milk fresh, un-pasteurized. The study dealt with the microbial quality of camel milk, which includes detection of pathogenic bacteria, enumeration of microorganisms (bacteria-yeast-moulds) that may cause changes to the milk, the distribution of bacteria in camel milk. The microbial quality of camels raw milk was investigated, 50 samples were analyzed for: Aerobic plates count, total coliform, total Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 5 publications
5
17
1
Order By: Relevance
“…The mean raw camel milk TBC observed in this study agrees with those reported by [19] (5.0 log CFU/ml), [15] (5.6–5.0 log CFU/ml), [20] (5.4 log CFU/ml), [21] (5.22 log CFU/ml) and [22] (3.0–5.0 log CFU/ml). The current mean TBC was in the range of EU acceptable limits for raw milk intended for direct human consumption and processing.…”
Section: Discussionsupporting
confidence: 91%
“…The mean raw camel milk TBC observed in this study agrees with those reported by [19] (5.0 log CFU/ml), [15] (5.6–5.0 log CFU/ml), [20] (5.4 log CFU/ml), [21] (5.22 log CFU/ml) and [22] (3.0–5.0 log CFU/ml). The current mean TBC was in the range of EU acceptable limits for raw milk intended for direct human consumption and processing.…”
Section: Discussionsupporting
confidence: 91%
“…Merin, Sela, Rosen, Pinto, and Leitner (2005) reported that camel milk bacterial quality is often not up to the accepted standards of bovine milk which suggests that milk from individual producers should not exceed 1 x 10 5 cfu mL −1 prior to commingling and 3 x 10 5 cfu mL −1 as commingled milk prior to pasteurization. It is also in line with the value 5.25 log 10 cfu mL −1 for aerobic plate count reported by Omer and Eltinay (2008) for camel milk in the United Arab Emirates. However, it is lower than the total bacterial counts of Somali camel milk collected from production farms (7.43 log 10 cfu mL −1 ), a primary collection site (8.84 log 10 cfu mL −1 ), a local market (8.83 log 10 cfu mL −1 ) and a distance market (9.23 log 10 cfu mL −1 ) (Younan et al, 2004).…”
Section: Physical Properties Of Camel Milksupporting
confidence: 90%
“…Disinfectant solution (Safflon 20%) was used to wash the udder before milk collection. Autoclaveable plastic containers (1000 mL) were used for the collection of samples and sterilized at 121°C for 20 min (16). Whole milk was converted into skim milk by centrifugation at 4000 g for 10 min at 15°C and then stored at −20°C.…”
Section: Methodsmentioning
confidence: 99%